(3TQW HbGA GdTiA Ydi MGdg ,Ch, fXQjI JZjQ GdXQha ai GdbGfhf GdOhdi (B/s - (3LYaQ YHO GdSdGe Ydis; (3MGeO SdWGfs [(3eTQa(B]s; (3eMeO MGaX ZGfes [(3eTQa(B]s; (3YGFTI QGJHs [(3eTQa(B]s (1970)
(3OC GdHGMK GdQSdI HaUd JegjOi (B: (3GdeQGMd GdJi eQ HgG fXQjI JZjQ GdXQha ai Gdabg GdOhdi ,hKdGKI GbSGe (B: (3GdGhd (B: (3GdGSGS Gdabgi dfXQjI JZjQ GdXQha , GdKGfi (B: (3GdGSGS GdYedi dfXQjI JZjQ GdXQha , GdKGdK (B: (3GdVhGHW GdbGfhfjI GdJi jNVY dgG JWHjb JZjQ GdXQha s
(3CWQhMI (B((3OcJhQGI (B)- (3LGeYI GdbGgQI(B. (3cdjI GdMbhb(B. (3bSe GdbGfhf GdOhdi GdYGes
Keywords: (3GdbGfhf GdOhdis; (3GdeYGgOGJ GdOhdjIs; (3GdYdGbGJ GdOhdjIs; (3GdeLJeY GdOhdis